Role of Statins on the Prevention of Coronary Spasm - Yoshimura, Michihiro (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2008)
Coronary spasm is involved in the pathogenesis of angina pectoris, acute myocardial infarction and sudden death. It has been revealed that endothelial function was reduced in patients with coronary spasm. Nitric oxide is a key molecule in the pathogenesis of coronary spasm; and the T-786→C polymorphism of the eNOS gene is strongly associated with coronary spasm. However, its precise mechanism(s) remains largely unknown. Also, a therapeutic strategy of coronary spasm has not been well established. HMG-CoA reductase inhibitors (statins) increase endothelial nitric oxide (NO) production, although the precise mechanism of this statin induced increase in NO production remains to be elucidated. We examined endothelial nitric oxide synthase (eNOS) mRNA levels, mRNA stability and the transcriptional activities of the eNOS gene in human umbilical vein endothelial cells treated with fluvastatin and simvastatin. We further examined whether the effects of these statins differ dependent upon the T -786→C polymorphism in the eNOS gene, and whether these statins affect gene expression of replication protein A1 (RPA1), which is known to reduce the transcriptional activity of the eNOS gene with the -786C allele. Utilizing the real-time reverse transcription-polymerase chain reaction, fluvastatin significantly increased eNOS mRNA levels and mRNA stability, and decreased RPA1 mRNA levels. As a result, fluvastatin increased eNOS mRNA levels by enhancing both the transcriptional activity and mRNA stability. The effect of fluvastatin on the transcriptional activity was augmented in the -786C/C genotype, probably because of a decrease in RPA1 gene expression. Simvastatin increased eNOS mRNA levels only by enhancing mRNA stability. The present study suggests that fluvastatin increases endothelial NO activity and thus may be more beneficial to patients with the -786C allele.